Analisis Pengaruh Pendidikan, Kesehatan, Sanitasi dan Rata-Rata Jumlah Anggota Keluarga Per Rumah Tangga terhadap Kemiskinan di Indonesia - Bagus Adhitya; Agus Prabawa; Heris Kencana (Universitas Batanghari Jambi, 2022)
This research is entitled Analysis of the Effect of Education, Health, Sanitation and Average Number of Family Members per Household on Poverty in Indonesia in 2013-2020. The location used in this study is Indonesia and the population in this study is 34 provinces. The data used in this study are secondary data obtained from the Central Bureau of Statistics in 2013-2020 as well as journals related to this research. The method used is Multiple Linear Regression with Panel Data approach which is processed using Eviews-10 software. The results of this study indicate that the fixed effect model is the best model with results showing that partially education and sanitation variables have a negative and significant effect. The results of this study support the poverty circle theory and the theory of human capital. Education is one of the human capital to increase productivity, with good productivity it will affect work and income which can later be used as a reference to get out of poverty. The sanitation variable supports the theory of human capital and has a relationship with public health which will also affect the quality of community productivity. Meanwhile, health variables and the average number of family members per household have no effect on poverty in Indonesia in 2013-2020. The implication of this research is that the government is expected to provide adequate educational facilities and provide counseling about the importance of sanitation to health in reducing poverty. The limitations of this study are that it only uses four independent variables and the period of time used is only 8 years.